ANALISIS PEMETAAN KESUKAAN KONSUMEN PADA PRODUK KERIPIK UBI KAYU ORIGINAL DI KALANGAN MAHASISWA FAKULTAS PERTANIAN UNIVERSITAS RIAU - Rici ' Mainaki; Fajar ' Restuhadi; Evy ' Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to determine the position of a product and attribute of cassava chips in the market, such as cassava chips Ojo Lali, Dolphins, Grace, Leni Snacks, Qtela, Kingkong, and Primadona. It aims to determine the level of consumer preference towards a product. Besides there was still a lack of effort in developing the product by the manufacturer at this time. This research was conducted by using internal and external preference mapping among seven different brand of cassava chips products. Sensory analysis used was hedonic test and descriptive test involving Riau University students as respondents. The results of hedonic test were analyzed using Agglomerative Hierarchical Clustering (AHC) and the results of the descriptive test were analyzed using Principal Component Analysis (PCA). The sensory attributes used on the product chips were color, greasy, sweetness, bitter, salty, crunchy, brittle, thickness, taste cassava,and rancidity. The conclusion of this results was product Qtela chips and Leni Snacks. keyword: Original cassava chips, preference mapping